Impact of macroeconomic variables on financial performance of unit trust in Malaysia / Muhammad Fadhli Abdullah - Abdullah, Muhammad Fadhli (2022)
Unit trust fund has been growing exponentially since 2007. This paper investigates the relationship between unit trust's net asset value (NAV) growth as the focus variable along with other control variables such as, Brent oil prices, Malaysia Interest Rate, USD/MYR exchange rate and inflation rate. Revealing the relationship will give us the right steps to build a stable index. This research presents a study of unit trust performance from the year 2000 to the year 2020. The whole year that has been observed for this research is twenty years. Moreover, this research uses secondary sources, and the data and information have been obtained via databases, other publications, and articles. All of the information gathered came from Google Scholar, Trading Economic, and Investing.com. In addition, the study employs descriptive analysis, correlation analysis, regression analysis, F-test, T-test, multicollinearity test and coefficient of determination (R2) to determine whether the independent variables are significant or insignificant towards the Malaysia unit trust performance. Therefore, it is concluded that the most important factors affecting the performance of unit trusts are the exchange rate, inflation rate and Brent crude price. This index is unaffected by interest rates in Malaysia.